The Apoptosis of Liver Cancer Cells Promoted by Curcumin/TPP-CZL Nanomicelles With Mitochondrial Targeting Function - Li, Wanyu; Chen, Yanan; He, Kun; Cao, Tianshou; Song, Daibo; Yang, Huiling; Li, Li; Lin, Jiantao (Frontiers in Bioengineering and Biotechnology, 2022)
The mitochondrion is one of the most important cellular organelles, many drugs work by acting on mitochondria. Curcumin (Cur) induced apoptosis of HepG-2 in liver cancer cells is closely related to the function of inhibiting mitochondria. However, mitochondrion-targeting curcumin delivery system was rare been reported. It is important to develop a high-efficiency mitochondrion-targeting curcumin vector that can deliver curcumin into mitochondrion directly. Here, special mitochondrion-targeting deliver system based on triphenylphosphine bromide (TPP)-chitosan-g-Poly-(N-3-carbobenzyloxy-L-lysine) (CS-g-PZLL) with TPP functional on the surface is designed to perform highly efficient mitochondria-targeting delivery for effective liver cancer cell killing in vitro. The TEM images showed that the nanomicelles were spherical; The results of fluorescence test showed that TPP-CS-g-PZLL nanomicelles could promote the cellular uptake of drugs, and finally targeted to the mitochondria; The results of cell survival rate and hoechst staining showed that curcumin/TPP-CS-g-PZLL nanomicelles could promote the apoptosis of liver cancer cells. Curcumin/TPP-CS-g-PZLL nanomicelles could significantly reduce the mitochondrial membrane potential, increase the expression of pro apoptotic protein Bcl-2 and reduce the expression of anti apoptotic Bax protein, these results were significantly better than curcumin/CS-g-PZLL nanomicelles and curcumin. It is a potential drug delivery system with high efficiency to target mitochondria of liver cancer cells.